Small Fibre Involvement in Multifocal Motor Neuropathy Explored with Sudoscan: A Single-Centre Experience - Luigetti, Marco (Diagnostics (Basel), 2020)
Objective: Multifocal motor neuropathy (MMN) is a rare inflammatory neuropathy, clinically characterized by exclusive motor involvement. We wished to evaluate the possible presence of sensory dysfunction, including the evaluation of small fibres, after a long-term disease course. Patients and methods: seven MMN patients, regularly followed in our Neurology Department, underwent clinical evaluation, neurophysiological examination by nerve conduction studies (NCSs), and Sudoscan. We compared neurophysiological data with a group of patients with other disorders of the peripheral nervous system. Results: NCSs showed a reduction of sensory nerve action potential amplitude in 2/7 MMN patients. Sudoscan showed borderline electrochemical skin conductance (ESC) values in 3/7 MMN patients (two of them with abnormal sensory NCSs). Conclusions: Our results confirm that sensory involvement may be found in some MMN after a long-term disease course, and it could also involve the small fibres.